1994
DOI: 10.1063/1.468181
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational predissociation dynamics of the He79Br2 van der Waals molecule near the B state dissociation limit: Binding energies, lifetimes, and implications for the rare gas–halogen potential

Abstract: Excitation spectra of the He79Br2 complex have been obtained for the B state vibrational levels v′=34–48 using the pump–probe spectroscopic technique. The Δv=−1 channel for vibrational predissociation is closed for levels v′=45 and higher. The B and X state van der Waals binding energies are determined to be 13.5±1.0 and 17.0±1.5 cm−1, respectively. Lifetimes for vibrational predissociation were found to range from 5.3 ps for v′=34 to 1.8 ps for v′=44. For v′=45 the lifetime increases to 3.8 ps due to the clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 52 publications
6
10
0
Order By: Relevance
“…However, when Jahn et al measured lifetimes of the 34Յ Ј Յ 48 levels, their values were somewhat larger, and it was suggested that the values of van de Burgt et al were in error by a factor of two. 30 The new results presented here convinced us to reexamine the data reported by van de Burgt et al We used the PGOPHER program 44 and simulated the 20← 0 rotational contour of Ref. 43 using the experimental parameters also reported in the paper.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…However, when Jahn et al measured lifetimes of the 34Յ Ј Յ 48 levels, their values were somewhat larger, and it was suggested that the values of van de Burgt et al were in error by a factor of two. 30 The new results presented here convinced us to reexamine the data reported by van de Burgt et al We used the PGOPHER program 44 and simulated the 20← 0 rotational contour of Ref. 43 using the experimental parameters also reported in the paper.…”
Section: Resultssupporting
confidence: 67%
“…29 and 31͒ and Ј = 45 for HeBr 2 . 30 We confirmed that for the Ј = 15 and 20 levels of NeBr 2 the ⌬Ј = −2 process accounts for only about 5% and 13% of the VP products, respectively. This is in good agreement with quantum dynamics calculations, where for Ј = 20 approximately 12% of the VP products undergo ⌬Ј = −2 dissociation.…”
Section: Resultssupporting
confidence: 65%
“…These shifts have been measured later by Sharfin et al and a lower value (by 1.2 cm −1 ) than the one used by Blazy et al has been obtained for the v = 62 level. Thus, a revised value of 17.6 ± 1.0 cm −1 has been proposed for the D 0 of the ground HeI 2 [30]. We should note that our prediction of 15.38 cm −1 for the D 0 binding energy is very close to the lower bound of the later experimental value (see table 5).…”
Section: Bound State Calculationssupporting
confidence: 83%
“…Their analysis indicates that the molecule on both ground and B excited state has a nonlinear structure and vibrationally average configurations have been determined. The other data available from these studies are blue-shift values for low and high v levels [28,29] and the X and B binding energies [28,30]. Recent experimental studies by Loomis and co-workers in the B ← X spectrum have shown that spectral features are associated with transitions of multiple conformers of several He-X Y complexes [8], and binding energies and structures of such isomers reported for HeI 2 [31].…”
Section: Introductionmentioning
confidence: 99%
“…11) but later revised to D 0 = 17.6 ± 1.0 cm −1 . 12 The most recent experimental binding energy, reported by the Loomis group, 13 amounts to 16.6 ± 0.6 cm −1 for the C 2v conformer and 16.3 ± 0.6 cm −1 for the linear conformer. The double minimum topology of the potential energy surface (PES), an interesting feature per se, was a known experimental fact from the studies on Ar-I 2 (Refs.…”
Section: Introductionmentioning
confidence: 99%